Recent trends in embryo disposition choices made by patients following in vitro fertilization - Alexander, Vinita M. (J Assist Reprod Genet, 2020)
PURPOSE: To assess longitudinal trends in in vitro fertilization (IVF) patients’ choices for disposing of cryopreserved embryos. METHODS: This is a retrospective cohort study of embryo disposition forms submitted between January 2000 and February 2020 at a university-based fertility clinic. Primary outcome was disposition decision. Binary and multivariable logistic regression were performed to determine odds ratios (OR) for decisions according to female age, education, race, religion, state of residence, area deprivation index based on zip code, and IVF pregnancy history. We also assessed disposition year, storage duration, and number of stored embryos. RESULTS: Forms were reviewed from 615 patients; 50.6% chose to discard embryos, 45.4% donated to research, and 4.1% chose reproductive donation. In the regression model, two factors were significantly associated with donation to research: female listing “no preference” or declining to list religious preference (OR 2.56, 95%CI 1.44–4.54) and live birth of multiples after IVF (OR 1.58, 95%CI 1.05–2.36). Before 2012, females younger than age 30 at storage were equally likely to choose to donate embryos to research as discard them. However, between 2013 and 2020, females younger than 30 were significantly more likely to discard than donate embryos for research (OR 2.87, 95%CI 1.13–7.28). CONCLUSION: Since 2013, the majority of patients younger than 30 at storage have chosen to discard cryopreserved embryos. Before then, patients were more likely to donate embryos for research. To ensure sufficient embryos are available for research, young patients, who are most likely to have cryopreserved embryos, should be counseled about options for donation.